Building integrated agri food chains between Asia and Brazil - Jank, Marcos S. (2018)
Marcos S. Jank SPECIAL EVENT Transforming Agriculture: Experiences and Insights from Brazil and Beyond Co-Organized by IFPRI and Embrapa MAY 15, 2018 - 12:15 PM TO 01:45 PM EDT